Environmental impact assessments and mitigation / Musaida Mercy Manyuchi, PhD, Charles Mbohwa, PhD, Edison Muzenda, PhD and Nita Sukdeo, PhD. - Manyuchi, Musaida Mercy; Mbohwa, Charles; Muzenda, Edison; Sukdeo, Nita (CRC Press, 2021)
'Environmental Impact Assessments and Mitigation' examines various assessments for developmental projects in the housing, mining, energy, and waste management areas. As the world continues to shift toward concerns over climate change and environmental protection issues, developmental projects must have environmental impact assessments (EIA) conducted as well as environmental management plans (EMP). This book describes how all phases of a project, from planning, to operation, to post operation, must consider potential environmental impacts and their mitigation.